Musical Entanglements between Germany and East Asia
XIX, 303 p. 6 illus.
Keywords: This edited volume explores musical encounters and entanglements between Germany and East Asian nations from 1900 to the present. In so doing, it speaks to their dynamic and multi-faceted musical relations in multiple ways. Despite East Asia and Germany being located at opposite ends of the globe, German music has found remarkably fertile soil in East Asia. East Asians have enthusiastically adopted it, while at the same time adding their own musical interpretations. These musical encounters have produced compositions that reflect this mutual influence, stimulating and enriching each other through their entanglement. After more than a century of entanglement, Germany and East Asia have become kindred musical spirits. .